2017
DOI: 10.1002/med.21458
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of natural and synthetic neuroprotective steroids against neurodegenerative disorders: A literature review

Abstract: Neurodegeneration is a complex process, which leads to progressive brain damage due to loss of neurons. Despite exhaustive research, the cause of neuronal loss in various degenerative disorders is not entirely understood. Neuroprotective steroids constitute an important line of attack, which could play a major role against the common mechanisms associated with various neurodegenerative disorders like Alzheimer's disease, Parkinson's disease, Huntington's disease, and amyotrophic lateral sclerosis. Natural endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 212 publications
(371 reference statements)
0
23
0
Order By: Relevance
“…Sleep disturbance; 2. daytime sleepiness; 3. fatigue and exhaustion; 4. low productivity; 5. headache; 6. perspiration; 7. vertigo; 8. faint feeling; 9. vomiting and nausea after anger; 10. hot and cold flashes; 11. shivers, inner need; 12. inattention and lack of concentration; 13. irritability and short temper; 14. memory retention; 15. backbone, muscle, and joint pain; 16. heart palpitations, heart pain; The intensity of the symptoms was self-estimated by patients using a 4-level scale: 0 = no, 1 = mild, 2 = high, 3 = extreme. The total score (from the viewpoint of neurotic tendency) was interpreted as follows: Normal (0-11), Mildly neurotic (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Highly neurotic (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), Extremely neurotic (>34). The somatic and psychosomatic disturbances were reflected in questions 1-11 and 12-22, respectively, while psychiatric symptoms were represented by questions 23-33.…”
Section: Neurotic Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disturbance; 2. daytime sleepiness; 3. fatigue and exhaustion; 4. low productivity; 5. headache; 6. perspiration; 7. vertigo; 8. faint feeling; 9. vomiting and nausea after anger; 10. hot and cold flashes; 11. shivers, inner need; 12. inattention and lack of concentration; 13. irritability and short temper; 14. memory retention; 15. backbone, muscle, and joint pain; 16. heart palpitations, heart pain; The intensity of the symptoms was self-estimated by patients using a 4-level scale: 0 = no, 1 = mild, 2 = high, 3 = extreme. The total score (from the viewpoint of neurotic tendency) was interpreted as follows: Normal (0-11), Mildly neurotic (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Highly neurotic (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), Extremely neurotic (>34). The somatic and psychosomatic disturbances were reflected in questions 1-11 and 12-22, respectively, while psychiatric symptoms were represented by questions 23-33.…”
Section: Neurotic Scoresmentioning
confidence: 99%
“…The data from the FZ as reported by Siriani et al [13] showed increased mRNA expression of the genes needed for DHEAS production, such as steroidogenic acute regulatory protein, cholesterol desmolase (CYP11A1), steroid C17-hydroxylase-C17,20-lyase (CYP17A1), and type 2A1 steroid sulfotransferase (SULT2A1), as well as the upregulation of type 1 CRH receptors after 24 h treatment of FZ cells with CRH, CRH-related peptide urocortin or ACTH. The various adrenal steroids that have synthesis controlled by CRH and ACTH as well as their metabolites may operate as neuroactive [14], neuroprotective [15] and immunoprotective [6] substances, affecting the somatic, psychosomatic and psychiatric health of patients [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many natural and synthetic drugs have been identified to affect processes such as oxidative stress to inhibit the neurodegenerative mechanisms underlying MS. In this context, it has been depicted that antioxidant molecules and compounds, which can reduce oxidative stress and free radicals, may be used as potential strategies against neurodegenerative diseases, particularly MS …”
Section: Introductionmentioning
confidence: 99%
“…The synergistic effects of these immunological responses in CNS and their signaling pathways are presented as critical factors in the progression of neuronal degradation and DNA fragmentation in MS. [15] In recent years, many natural and synthetic drugs have been identified to affect processes such as oxidative stress to inhibit the neurodegenerative mechanisms underlying MS. In this context, it has been depicted that antioxidant molecules and compounds, which can reduce oxidative stress and free radicals, may be used as potential strategies against neurodegenerative diseases, particularly MS. [16] Saffron is one of the natural remedies in traditional medicine being used for various purposes such as sedative, antidepressants, antispasmodic, in addition to the treatment of scarlet fever, chickenpox, colds, asthma, eye, and cardiovascular diseases, and also cancers. [17][18][19][20] The analysis of the chemical composition of saffron has shown that this medicinal plant contains a large number of active and potent biological compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These encouraging findings let us to investigate whether some of our ANS may optimally exert a neuroprotective action by preventing neuronal death without promoting the cell proliferation that usually represents an undesirable effect hampering the treatment of neurodegenerative processes in various pathological situations, including cancers. Therefore, we compared the ability of our ANS and AP to protect against oxidative stress‐induced neuronal death that is pivotally involved in the patho‐physiological mechanisms of various neurodegenerative disorders . Our results clearly showed that both O‐allyl ANS (BR351 and BR297) had notable advantages over AP with regard to the protection of SH‐SY5Y cells against oxidative stress‐induced death.…”
Section: Discussionmentioning
confidence: 86%